The primary gene pool of cassava (Manihot esculenta Crantz). - ALLEM, A. C. (2000)
A crop gene pool comprises three distinct categories of gene suppliers, primary, secondary, and tertiary gene pools. The primary gene pool (GP-1) is composed of gene reservoirs that cross easily with the domesticate and the crosses produce fertile offspring regularly. The secondary (GP-2) and tertiary (GP-3) gene pools comprise gene sources that cross with variable degrees of diffilculty with the crop species, this implies less close genetic distances. The GP-1 is further subdivided in cultivated and wild gene pools. The cultivated gene pool englobes commercial stocks of the crop besides indigenous landraces and folk varieties of the domesticate. The wild GP-1 of a crop comprises putative ancestors and closely related species that show a fair degree of fertile relationships with the domesticate. Two Douth American wild subspecies of cassava (M. flabellifolia and M. peruviana) are natural members of the wild GP-1 of the species. Another Brazilian species (M. pruinosa) is so close morphologically to the two wild subspecies of cassava that it may turn out another member of the wild GP-1 of the indigen. The GP-2 of cassava is more difficult to delimit as few species have been tested for genetic compatibility. Biosystematic crosses carried out between the crop and a number of wild species suggest a dozen of them as components of the GP-2, the majority are Brazilian species.